2019
DOI: 10.1055/a-0957-3005
|View full text |Cite
|
Sign up to set email alerts
|

Does endoscopic ultrasound-guided fine needle biopsy using a Franseen needle really offer high diagnostic accuracy? A propensity-matched analysis

Abstract: Background and study aims This study aimed to investigate the diagnostic accuracy and utility of endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) performed using a Franseen needle on solid pancreatic lesions. Patients and methods This study included 132 consecutive lesions sampled by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) using a 22-G conventional needle and 95 consecutive lesions evaluated by EUS-FNB using a 22-G Franseen needle to evaluate solid pancreatic lesions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…We showed in our study a diagnostic accuracy of 85%, whereas the diagnostic accuracy for pancreatic lesions in other series was reported between 90% and 97.9%[ 5 , 11 , 14 , 16 , 18 , 19 , 24 , 26 , 28 ]. Bang et al[ 5 ] reported a significantly higher diagnostic accuracy of Franseen needle over FNA needle (97.8% vs 82.6%, P = 0.03), whereas three other series demonstrated an equal to higher diagnostic accuracy, though not significantly[ 14 , 26 , 28 ].…”
Section: Discussioncontrasting
confidence: 64%
“…We showed in our study a diagnostic accuracy of 85%, whereas the diagnostic accuracy for pancreatic lesions in other series was reported between 90% and 97.9%[ 5 , 11 , 14 , 16 , 18 , 19 , 24 , 26 , 28 ]. Bang et al[ 5 ] reported a significantly higher diagnostic accuracy of Franseen needle over FNA needle (97.8% vs 82.6%, P = 0.03), whereas three other series demonstrated an equal to higher diagnostic accuracy, though not significantly[ 14 , 26 , 28 ].…”
Section: Discussioncontrasting
confidence: 64%
“…Furthermore, obtaining a sufficient core sample can enable genetic analysis and molecular profiling [ 8 , 14 ], which can contribute to personalized treatment selection. Several studies have already confirmed the efficacy of the Franseen needle [ 15 , 16 , 17 ]. A meta-analysis of 15 studies with 1024 patients revealed that, relative to FNA needles and in the absence of ROSE, FNB needles provided better diagnostic adequacy for solid pancreatic lesions and required fewer needle passes to establish the diagnosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considering the tip structure of the AC22, this needle might be more effective than other types particularly for cases in which a long puncture stroke length cannot be secured. Fujita et al [ 38 ] compared the diagnostic accuracy between the AC22 and a conventional needle and found no difference between the two needles for > 20-mm tumors; however, there was a significant difference for < 19-mm tumors. There was no significant difference in the histological accuracy between the PC20 and AC22 in the present study ( p = 0.02, p -adj = 0.06).…”
Section: Discussionmentioning
confidence: 99%